Effect of Collagen Cross-Linking on Alkali Burn-Induced Corneal Neovascularization in Rabbits - Xiaoying Xu; Taixiang Liu; Haixiang Li (Journal of Ophthalmology)
Objective. This study aims at investigating the effects and molecular mechanism of riboflavin-ultraviolet-A-induced cross-linking (corneal collagen cross-linking, CXL) on corneal neovascularization (CNV) in a rabbit alkali burn model. Methods. A total of 60 rabbits were injured with alkali burns to induce CNV in the right eye and were randomly divided into six groups: Group A—injury and no treatment; Groups B, C, and D—CXL treatment for 30 min, 15 min, and 45 min administered immediately after injury, respectively; and Groups E and F—CXL treatment for 30 min administered 1 day and 3 days after injury, respectively. CNV area, corneal edema, and corneal epithelial defects were observed on days 4, 7, 10, and 14 after injury. Western blot was used to detect expression of the vascular endothelial growth factor (VEGF), matrix metalloproteinase-2 (MMP-2), matrix metalloproteinase-2 (MMP-9), and tissue inhibitor of metalloproteinases 1 (TIMP-1) at 7 and 14 days after injury. Results. CXL treatment decreased CNV and corneal edema in all groups compared to Group A. On day 7, MMP-9 expression was significantly increased in all CXL treatment groups, and TIMP-1 was upregulated in Groups D and F compared to Group A. In addition, VEGF, MMP-2, MMP-9, and TIMP-1 expression were increased in Group A on day 14 after injury. Conclusions. Our results indicate that riboflavin-ultraviolet-A-induced cross-linking (corneal collagen cross-linking, CXL) significantly inhibits alkali burn-induced CNV in rabbits, possibly through downregulating VEGF, MMP-2, MMP-9, and TIMP-1 expression.